Letter to: Gastric Glomus Tumor: Report of a Case - Young, Teck Seong; Lee, Shi Yun; Ng, Chiak Yot; Hayati, Firdaus (Bangladesh Journal of Medical Science, 2022)
Abstract not available Bangladesh Journal of Medical Science Vol. 21 No. 02 April’22 Page : 477-478